Effects of the oral testosterone undecanoate Kyzatrex™ on ambulatory blood pressure in hypogonadal men - William B. White; James S. Bernstein; Roger Rittmaster; Om Dhingra (The Journal of Clinical Hypertension, 2021)
Abstract Testosterone replacement therapies have been shown to increase blood pressure (BP) in hypogonadal men. We studied the effects of a new formulation of testosterone undecanoate (Kyzatrex™) on ambulatory blood pressure (ABP) and heart rate, in 155 men with hypogonadism (mean age, 50.5 years, 76.8% white, 36.1% on antihypertensive therapy). The ABP, heart rate and clinical assessments were obtained at baseline and following 120 and 180 days of therapy. Mean changes from baseline in 24‐h ambulatory systolic BP of 1.7 mmHg (95% CI, 0.3, 3.1) at day 120 and 1.8 mmHg (95% CI, 0.3, 3.2) at day 180 were observed post‐treatment. For those men on antihypertensive drug therapy, increases in mean 24‐h systolic BP were greater than those not taking antihypertensive drugs (3.4 vs 0.7 mmHg at day 120 and 3.1 vs 1.0 mmHg at day 180, respectively). Changes from baseline in 24‐h diastolic BP and heart rate at day 120 were smaller (<1 mmHg and <1 beat/min, respectively). There were no relationships observed between testosterone concentration or hemoglobin levels with ABP. Multivariable analyses showed that baseline ambulatory BP and antihypertensive therapy were significantly correlated with BP changes. These data demonstrate small increases in ambulatory BP following 120 days on this oral testosterone undecanoate with no further changes at 180 days. Changes in ambulatory BP were minimal in patients not taking antihypertensive therapy.